Growth and Methanogenesis by Methanosarcina Strain 227 on Acetate and Methanol - Smith, Michael R. (1978)
Methanosarcina strain 227 exhibited exponential growth on sodium acetate in the absence of added H(2). Under these conditions, rates of methanogenesis were limited by concentrations of acetate below 0.05 M. One mole of methane was formed per mole of acetate consumed. Additional evidence from radioactive labeling studies indicated that sufficient energy for growth was obtained by the decarboxylation of acetate. Diauxic growth and sequential methanogenesis from methanol followed by acetate occurred in the presence of mixtures of methanol and acetate. Detailed studies showed that methanol-grown cells did not metabolize acetate in the presence of methanol, although acetate-grown cells did metabolize methanol and acetate simultaneously before shifting to methanol. Acetate catabolism appeared to be regulated in response to the presence of better metabolizable substrates such as methanol or H(2)-CO(2) by a mechanism resembling catabolite repression. Inhibition of methanogenesis from acetate by 2-bromoethanesulfonate, an analog of coenzyme M, was reversed by addition of coenzyme M. Labeling studies also showed that methanol may lie on the acetate pathway. These results suggested that methanogenesis from acetate, methanol, and H(2)-CO(2) may have some steps in common, as originally proposed by Barker. Studies with various inhibitors, together with molar growth yield data, suggest a role for electron transport mechanisms in energy metabolism during methanogenesis from methanol, acetate, and H(2)-CO(2).